DECODING THE STRUCTURAL AND SEMANTIC FEATURES OF PHRASEOLOGICAL UNITS IN THE DOMAIN OF CLOTHING IN ENGLISH - Mavlonova Nozliya Shodmurodova (Western European Studies, 2024)
This article delves into the structural and semantic intricacies of phraseological units within the domain of clothing in English. Drawing upon a methodological framework encompassing literature review and data analysis, the study identifies and categorizes these linguistic expressions based on their fixedness, figurativeness, lexical specificity, cultural references, social connotations, and functional roles. Results reveal that clothing-related phraseological units exhibit rigid structures, employ figurative language, feature specialized vocabulary, reflect cultural practices and social dynamics, and fulfill pragmatic functions. Through a comprehensive discussion, the article highlights the significance of these expressions as linguistic artifacts, shedding light on their role in communication, cultural representation, and societal understanding. Understanding and appreciating the structural and semantic features of clothing-themed phraseological units enrich language proficiency and foster cross-cultural awareness, offering valuable insights into the intricate interplay between language, culture, and society
Keywords: Phraseological units; Idiomatic expressions; Clothing; Attire